Liquidity and Stock Returns - Zou, Qianyun (2009)
This paper provides an analysis of liquidity premium using monthly data of the U.K. stock market from 1993 to 2008. The liquidity measures are the relative bid-ask spread and the turnover rate. Overall the evidence suggests that there is no significant relation between liquidity level and asset returns. In the time-series analysis in which a portfolio method is involved, for one-month holding period there is no significant liquidity premium associated with either liquidity measure. Consistently, the results of cross-sectional regressions also suggest that liquidity does not have explanatory power in the cross-sectional variation of asset returns and, if anything, the opposite is observed. In addition, the book-to-market ratio proves to be efficient in explaining expected return, whereas the influence of firm size on returns is only significant in January months over the second half of sample period from 2001 to 2008.